Partial Discharge Source Identification Using Pulse Height Distribution for Diagnosis in High Voltage Rotating Machines - Deshpande, Amol; Chimurkar, Priya; Rathod, Kiran; Cheeran, A. N.; Mangalvedekar, H. A. (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2025)
Electrical discharges that are localized in nature and do not completely bridge the electrodes are called as Partial Discharge (PD). PD is the major cause of insulation degradation, and it may eventually lead to system breakdown. Therefore, monitoring of such discharges is important considering efficient diagnosis of high voltage insulation systems. Depending on the source of discharge, there are types of discharges generally occurring in rotating machines viz. Slot Discharge, Delamination, void discharge etc. The plot of count of PD pulses versus the PD magnitude is called the PD height distribution (PDHD) plot or Pulse Height Distribution (PHD) plot. This plot is derived from the actual measurement data on high voltage (HV) rotating machines and the results thus obtained are discussed in this research work. This plot is used to identify the presence of individual PD source or simultaneous occurrence of PD sources in the HV rotating machine. This is the novel contribution of this research work. Phase Resolved PD (PRPD) patterns are used to validate the results. The results for individual discharges and simultaneous discharges are discussed in this paper. The significance of pulse height analysis for diagnosis of HV rotating machines is discussed in this paper.